Surface modification of bacterial cellulose by nitrogen-containing plasma for improved interaction with cells - Pértile, Renata Aparecida Nedel (2010)
Bacterial cellulose (BC) membranes were modified with nitrogen plasma in order to enhance cell affinity. The surface properties of the untreated and plasma modified BC (BCP) were analyzed through contact angle measurements, X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM). The effect of the plasma treatment on the adhesion of microvascular (HMEC-1), neuroblast (N1E-115) and fibroblast (3T3) cell lines was analyzed. The nitrogen plasma treatment did not increase the wettability of the material, but increased the porosity and surface chemistry, as noticed by the presence of nitrogen. XPS analysis revealed the stability of the modified material along time and autoclave sterilization. The cell adhesion and proliferation of HMEC-1 and N1E-115 cells was significantly improved in the BCP, in contrast with the 3T3 cells, revealing a cell-specific effect. This work highlights the potential of plasma treatment for the modification of the BC surface properties, enhancing its potential for biomedical applications.